Efek Ekstrak Sambiloto (Andrographis paniculata Nees.) pada Ekspresi P53 dari Kanker Payudara Tikus yang Diinduksi DMBA - Yurika Sastyarina; Junaidi Khotib; Sukardiman Sukardiman (Journal of Tropical Pharmacy and Chemistry, 2011)
ABSTRACT It has been well documented that chemical carcinogen, 7.12 dimethylbenz-(a)anthracene (DMBA), plays a role in the incidence and growth of mammary cancer. Present study was designed to investigate the influence of Andrographis paniculata extract on telomerase activities on DMBA induced breast cancer in the female rat Sprague Dawley strain. DMBA-induced mammary cancer is a useful model to investigate the changes of epithelial cells that occur during mammary cancer progression. Mammary cancer model was induced 10 times twice a week by oral DMBA 20 mg/kg body weight. Mammary cancer occurred in 75 % animals nine weeks after oral administration of DMBA, it was represented with nodule on the mammary gland and the increasing of mammary gland volume compare with normal control F(1.8) = 731.711; p < 0.001. This study was also designed to investigate the effect of Andrographis paniculata extract mammary carcinoma induced by DMBA. Administration of three different dose of Andrographis paniculata (100 mg/kg, 300 mg/kg and 1000 mg/kg) had statistically different with mammary gland volume of DMBA treated rat F (4.17) = 92.777; p<0.05. So, Andrographis paniculata has significant effect on the treatment of DMBA-induced mammary carcinoma. The Epithelial cells were harvested on day 90 and stained with routine histology staining, hematoxylineosin, for morphological qualitative analysis, immunohistochemical examination. The lesions observed from the removed samples ranged widely from benign to malignant. The results showed that DMBA induce cell proliferation, nuclear irregularities, and numerous mitoses and induced cell necrosis. On immunohistochemical examination, it shows that Andrographis paniculata can stimulate of expression of p53 protein and increase the number of epithelial cells experience apoptosis. Key words: Sambiloto (Andrographis Paniculata Ness), DMBA, mammary cancer, p53 ABSTRAK Telah terdokumentasi dengan baik bahwa karsinogen kimia, 7,12 dimetilbenz(a)antrasena (DMBA), berperan dalam kejadian dan perkembangan kanker payudara. Penelitian ini dirancang untuk mengetahui pengaruh ekstrak Andrographis paniculata ekspresi p53 dan apoptosis pada kanker payudara tikus strain Sprague Dawley yang diinduksi DMBA. Kanker Payudara yang diinduksi DMBA adalah sebuah model yang berguna untuk mengetahui perubahan sel epitel yang terjadi selama perkembangan kanker payudara. Model Kanker Payudara diinduksi DMBA secara per oral 20 mg / kg 10 kali yaitu dua kali seminggu. Kanker Payudara terjadi pada 75% hewan pada sembilan minggu setelah pemberian oral DMBA, Hal itu diwakili dengan benjolan pada kelenjar susu dan meningkatnya volume kelenjar susu dibandingkan dengan F kontrol (1,8) = 731.711; p <0,001. Penelitian ini juga dirancang untuk mengetahui pengaruh ekstrak Andrographis paniculata pada kanker payudara yang diinduksi oleh DMBA. Pada pemeriksaan imunohistokimia, hal itu menunjukkan bahwa sambiloto dapat menurunkan enzim telomerase, meningkatkan ekspresi protein p53 dan meningkatkan jumlah apoptosis sel epitel. Kata Kunci: Sambiloto (Andrographis Paniculata. Ness), DMBA, Kanker payudara, p53